Assessment of the ability of formal seed companies to produce and distribute forage seeds in Uganda - Lukuyu, Ben A.; Namutebi, Patricia (Bioversity International and the International Center for Tropical Agriculture, 2021)
The information below was obtained through a survey carried out by a face to face interview using a questionnaire that was prepared to analyze the forage seed production and supply system in Uganda. Out of the 9 formal seed companies that sell forage seeds, only 6 like Robran Holdings Ltd, NARO Holdings Ltd, National Tree seed Centre, Rhino seeds, Sim law seeds and East Africa Seeds participated in the survey. The other 3 like Victoria seeds, FORESCO Uganda and grow more seeds and Chemicals had technical and administrative constraints that hindered their participation.